Flavonoides de Barbacenia blanchetii (velloziaceae) e avaliação do efeito inibitório sobre butirilcolinesterase - Barbosa, Jósquia dos Santos (2012)
Velloziaceae is a family of monocotyledons that represents an important source of flavonoids. Among this family genus, Barbacenia usually presents flavonoids with methoxy groups and/or sugar units. The flavonoids are secondary metabolites that can have pharmacological effects on the Central Nervous System (CNS), and as consequence, inhibit the butyrylcholinesterase (BuChE). This enzyme plays an important role in acetylcholine release in normal human brains and especially on those affected by Alzheimer’s disease. In this sense, the search for BuChE inhibitors has been one of the strategies to enhance acetylcholine levels in patients affected by this disease, mainly, in advanced pathological stages, when happens a low expression of acetylcholinesterase (AChE) and an improvement of BuChE. This work describes the analysis of flavonoids from B. blanchetii and evaluates the inhibition of BuChE activity by extracts, fractions and by the isolated flavonoid from this specie. The methanolic, ethyl acetate and methanol extracts where monitored by HPLC-DAD and the UV spectra showed absorptions in specific regions of flavonoid compounds. The methanolic extract showed high presence of flavonoids and significant maximum effect of BuChE inhibition in relation to the rest of the extracts. The methanolic extract was fractionated and among the present flavonoids, the 4′,5,7-trihidroxy-3′,5′-dimethoxiflavone was isolated and identified by chromatographic and spectrometric techniques (HPLC-DAD/MS/MS and NMR 1D and 2D). The extracts inhibit the BuChE activity in a dose-dependent. The fractions from methanolic extract also showed dose-dependent inhibition, although the flavonoid 4′,5,7-trihydroxy-3′,5′-dimethoxyflavone didn’t showed significant inhibitory effect.